MEMBANGUN KOMPETENSI ABAD 21 MELALUI METODE CONSTRUCTIVE CONTROVERSY PADA PEMBELAJARAN BAHASA INGGRIS - Leny Sri Wahyuni (Balai Diklat Keagamaan Bandung, 2020)
This study aims to describe an image of cooperative learning model application through constructive controversy method in building 21st century competencies towards English learning. This study uses descriptive qualitative which took place at the second grade of SMKN 1 Talaga, Majalengka. Collecting data is done by using observation, interview, and documentation. The results illustrate that the ability to communicate, collaborate, think critically, and creatively in students can be built through controversial issues which make them challenged to discuss actively, intensively, and comprehensively. The use of 'gambits' in form of asking and giving opinions is quite effective to encourage students to analyze (communicate actively and effectively) related to the issues raised, collaborate intensively on various ideas to make decisions, and formulate solutions by constructing ideas from various results of divergent thinking. Keywords: 21st century competencies; English learning; cooperative learning model; constructive controversy method; controversy issues